2015
DOI: 10.1007/s00737-015-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and suicidal ideation in pregnant women

Abstract: Intimate partner violence (IPV) during pregnancy is a major public health issue with significant implications for maternal mental health. Less studied is the association between IPV during pregnancy and suicidal ideation. This study reports the prevalence and correlates of suicidal ideation among low-income pregnant women receiving prenatal care at a university obstetrical clinic from February 2009 to March 2010. We performed a cross-sectional analysis of 166 women surveyed between 24 – 28 weeks gestation usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
71
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 43 publications
8
71
0
4
Order By: Relevance
“…Similarly, da Silva et al (da Silva et al, 2012) conducted a multivariate logistic regression analysis and found that those women who had not finished elementary school had an increased risk of suicidal ideation compared to those who did (OR=2.84, 95% CI: 1.51–5.34). These findings have been corroborated by a number of other investigators (Asad et al, 2010, Coelho et al, 2014, Alhusen et al, 2015, Newport et al, 2007, Gandhi et al, 2006). …”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Similarly, da Silva et al (da Silva et al, 2012) conducted a multivariate logistic regression analysis and found that those women who had not finished elementary school had an increased risk of suicidal ideation compared to those who did (OR=2.84, 95% CI: 1.51–5.34). These findings have been corroborated by a number of other investigators (Asad et al, 2010, Coelho et al, 2014, Alhusen et al, 2015, Newport et al, 2007, Gandhi et al, 2006). …”
Section: Resultssupporting
confidence: 78%
“…Furthermore, the authors reported that maternal exposure to verbal abuse was associated with 4.20-fold increased odds (OR=4.20, 95% CI: 2.47–7.15) of suicidal ideation. Alhusen et al (Alhusen et al, 2015) also found a strong association between intimate partner violence and suicidal ideation among pregnant women in the U.S. Using multivariate logistic regression, the authors found that intimate partner violence during pregnancy was associated with 9.37-fold increased odds of suicidal ideation (OR=9.37, 95% CI: 3.41–25.75) (Alhusen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations